2021
DOI: 10.1021/acsami.1c03903
|View full text |Cite
|
Sign up to set email alerts
|

Robust Protection of III–V Nanowires in Water Splitting by a Thin Compact TiO2 Layer

Abstract: Narrow-band-gap III–V semiconductor nanowires (NWs) with a suitable band structure and strong light-trapping ability are ideal for high-efficiency low-cost solar water-splitting systems. However, due to their nanoscale dimension, they suffer more severe corrosion by the electrolyte solution than the thin-film counterparts. Thus, short-term durability is the major obstacle for using these NWs for practical water-splitting applications. Here, we demonstrated for the first time that a thin layer (∼7 nm thick) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…The illumination source used was a 500 W Xe arc lamp (CEL-HXF300) with a AM 1.5 G filter. The measured potentials vs. Ag/AgCl were converted to the potentials vs. reversible hydrogen electrode (RHE) using the following Nernst equation: 25 E RHE = E Ag/AgCl + 0.059pH + E 0 Ag/AgCl …”
Section: Methodsmentioning
confidence: 99%
“…The illumination source used was a 500 W Xe arc lamp (CEL-HXF300) with a AM 1.5 G filter. The measured potentials vs. Ag/AgCl were converted to the potentials vs. reversible hydrogen electrode (RHE) using the following Nernst equation: 25 E RHE = E Ag/AgCl + 0.059pH + E 0 Ag/AgCl …”
Section: Methodsmentioning
confidence: 99%
“…The representative materials include Si and III‐V compound semiconductors, which possess tunable bandgaps for light absorption in the spirit of the well‐known band gap engineering including relatively narrow band gaps, e.g., 1.1 eV for Si, 1.05 eV for GaInAsP lattice‐matched to InP, 1.35 eV for InP, 1.42 eV for GaAs, or 1.90 to 2.23 eV for AlGaInP lattice‐matched to GaAs [28b,29] . For example, the GaAs‐ and Si‐based core‐shell PEC photoelectrodes had been reported by Cui's and Jaramillo's groups, respectively ( Figure ) [13a,22] . However, these materials usually suffer from corrosion during the PEC reactions.…”
Section: Core‐shell Tandem Nanostructured Photoelectrode For Pec Wate...mentioning
confidence: 99%
“…SEM a) and higher‐magnification TEM b) images of the GaAs NW/TiO 2 photoelectrode. Reproduced with permission [13a] . Copyright 2021, American Chemical Society.…”
Section: Core‐shell Tandem Nanostructured Photoelectrode For Pec Wate...mentioning
confidence: 99%
See 1 more Smart Citation
“…III–V nanowires (NWs) present a high aspect ratio improving their light-trapping efficiency and have a strong ability to be grown on low-cost silicon substrate, making them particularly attractive to design innovative photoelectrodes for light-driven water splitting . While many studies have been focusing on the use of III–V NWs as photoanodes for the OER, only few reports are available on the use of these materials as photocathodes for the HER. A recent work by Zhou et al indicated a significant enhancement of the STH efficiency, reaching performances close to 10% using the GaP NW combined with a complex heterostructure and band gap engineering . If the corrosion of these materials has limited the viability of their use in actual devices thus far, Cui et al recently demonstrated the possibility to overcome this issue by protecting the surface of the nanowires with a thin TiO 2 oxide layer .…”
Section: Introductionmentioning
confidence: 99%